Astaxanthin promotes locomotor function recovery and attenuates tissue damage in rats following spinal cord injury: a systematic review and trial sequential analysis - Zhou, Long-yun; Wu, Zi-ming; Chen, Xu-qing; Yu, Bin-bin; Pan, Meng-xiao; Fang, Lu; Li, Jian; Cui, Xue-jun; Yao, Min; Lu, Xiao (Frontiers in Neuroscience, 2023)
Spinal cord injury (SCI) is a catastrophic condition with few therapeutic options. Astaxanthin (AST), a natural nutritional supplement with powerful antioxidant activities, is finding its new application in the field of SCI. Here, we performed a systematic review to assess the neurological roles of AST in rats following SCI, and assessed the potential for clinical translation. Searches were conducted on PubMed, Embase, Cochrane Library, the Web of Science, China National Knowledge Infrastructure, WanFang data, Vip Journal Integration Platform, and SinoMed databases. Animal studies that evaluated the neurobiological roles of AST in a rat model of SCI were included. A total of 10 articles were included; most of them had moderate-to-high methodological quality, while the overall quality of evidence was not high. Generally, the meta-analyses revealed that rats treated with AST exhibited an increased Basso, Beattie, and Bresnahan (BBB) score compared with the controls, and the weighted mean differences (WMDs) between those two groups showed a gradual upward trend from days 7 (six studies, n = 88, WMD = 2.85, 95% CI = 1.83 to 3.87, p < 0.00001) to days 28 (five studies, n = 76, WMD = 6.42, 95% CI = 4.29 to 8.55, p < 0.00001) after treatment. AST treatment was associated with improved outcomes in spared white matter area, motor neuron survival, and SOD and MDA levels. Subgroup analyses indicated there were differences in the improvement of BBB scores between distinct injury types. The trial sequential analysis then firmly proved that AST could facilitate the locomotor recovery of rats following SCI. In addition, this review suggested that AST could modulate oxidative stress, neuroinflammation, neuron loss, and autophagy via multiple signaling pathways for treating SCI. Collectively, with a protective effect, good safety, and a systematic action mechanism, AST is a promising candidate for future clinical trials of SCI. Nonetheless, in light of the limitations of the included studies, larger and high-quality studies are needed for verification.